Manajemen Kesiswaan dalam Meningkatkan Kedisiplinan Peserta Didik - Subaidi Subaidi (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah kendari, 2023)
Through student management, this study seeks to explain why pupils at Al-Karimah Temuroso Guntur Demak Islamic Middle School have become more disciplined. In this study, a qualitative method with a descriptive type is used. Observational methods, interviews with foundation officials, school principals, and teachers as informants, as well as records in the form of teacher and student data, were utilized to collect the data. data analysis involving procedures like data review, data reduction, and verification/conclusion. First, Islamic Middle School Al-Karimah Temuroso Guntur Demak planned several actions to establish student discipline, according to the study's findings. Second, all these programs' implementations proceeded according to schedule. Thirdly, evaluating how well student activities are being implemented involves observing how students behave during school-sponsored Qur'anic recitation.